Plasma discharge and time-dependence of its effect to bacteria - Justan, I; Cernohorska, L; Dvorak, Z; Slavicek, P (Folia microbiologica, 2014)
Several types of plasma discharge have been proven to have a capacity for sterilization. Our goal is to introduce new nonthermal plasma pencil. We used it to sterilize different microbial populations with differing ages. We used a plasma discharge of the following characteristics: radio frequency barrier discharger at atmospheric pressure with a working frequency of 13.56 MHz, and the working gas used was argon. We performed 110 tests with the following microbial populations: Pseudomonas aeruginosa, Staphylococcus aureus, Proteus species, and Klebsiella pneumoniae. All populations were inoculated on the previous day and also on the day of our experiment. We made our evaluations the following day and also after 5 days, with all our microbial populations. Eradication of microbial populations is dependent on the plasma discharge exposure time in all cases. With regard to freshly inoculated microbes, we were able to sterilize agar with intensive exposure lasting for 10 s of colonies Pseudomonas, Proteus, and Klebsiella. The most resistant microbe seems to be S. aureus, which survives 5 s of coherent exposure in half of the cases. Using the lightest plasma discharge exposure, we achieved a maximum of 10(4)-10(5) CFU/mL (colony-forming unit - CFU). Regarding older microbial populations inoculated the day before the experiment, we can only decrease population growth to 10(5) CFU/mL approximately, but never completely sterilize. The plasma discharge with our characteristics could be used for the sterilization of the aforementioned superficially growing microbes, but does not sufficiently affect deeper layers and thus seems to be a limitation for eradication of the already erupted colonies.
Keywords: Electromagnetic Radiation; elektromagnetické záření; Sterilization; sterilizace; Bacteria